2011
DOI: 10.1080/10640266.2011.551632
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Residential Treatment for Anorexia Nervosa and Bulimia Nervosa

Abstract: We analyzed results from surveys of respondents who had completed ≥ 30 days of treatment at Monte Nido Residential Treatment Program over a 10 year period. Participants with anorexia nervosa (AN; n = 66) and bulimia nervosa (BN; n = 52) completed the Eating Disorders Inventory-2 (EDI-2), the Beck Depression Inventory (BDI), and a structured eating disorder assessment at admission and follow-up. Mean duration between discharge and last follow-up was 4.6 years and 3.8 years for AN and BN respectively. For AN the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…In DPP we found that lower frequency of vomiting trend significantly predicted better outcome. A similar result was found in a study on long-term outcome [37]; frequency of vomiting in BN at time of discharge from residential treatment was predictive of outcome at follow-up. Why we found fewer predictors in DPP could be that fewer analyses were performed for this group or that a more intensive treatment is less sensitive to patient characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…In DPP we found that lower frequency of vomiting trend significantly predicted better outcome. A similar result was found in a study on long-term outcome [37]; frequency of vomiting in BN at time of discharge from residential treatment was predictive of outcome at follow-up. Why we found fewer predictors in DPP could be that fewer analyses were performed for this group or that a more intensive treatment is less sensitive to patient characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…Half of deaths were due to suicide, while other causes included alcohol abuse or medical consequences of marasmic malnutrition [5]. Short-term evaluations showed good outcomes ranging from 18 [6] to 42 % [7]. The 4-year or 5-year clinical recovery rate was higher and it was influenced by the duration of follow-up [8][9][10][11].…”
Section: Introductionmentioning
confidence: 92%
“…Residential treatment programmes have been found to be effective in the treatment of AN and BN both post-treatment and at 3–4 year follow-up [101,102]. Treatment for EDs may also take place within substance abuse treatment programmes, however not all such programmes are equipped with adequate knowledge or resources [93].…”
Section: Reviewmentioning
confidence: 99%